Estresse de minoria, fatores familiares e saúde mental em homens homossexuais - Lawrence, Priscila (2017)
Sexual stigma and exposure to prejudice can have a negative impact on mental health and well-being of homosexual men. Theorizing about such impacts led to formulation of the minority stress model and studies that investigate the role played by family in relation to these experiences. This dissertation has the aim of verify and understand associations between exposure of prejudice and violence, family factors and mental health problems in homosexual men. Two empirical studies were developed. Study 1, entitled “Minority Stress, Parenting Stiles, Child Abuse and Mental Health in Homosexual Men”, aimed to investigate the association between minority stress, parenting styles, child abuse and indicators of mental health problems among homosexual men. The study design was quantitative, cross-sectional, correlational and retrospective. One hundred and one brazilian men self-identified as homosexual with ages between 18 and 55 were participants. Instruments included: a) Sociodemographic questionnaire; b) Enacted Stigma Scale; c) Shortened Internalized Homonegativity Scale; d) Concealment of Sexual Identity Inventory; e) Respondingness and Demandingness Parental Styles Scale; f) Maltreatment and Abuse Chronology of Exposure Scale (MACE); g) Depression Anxiety Stress Scale (DASS-21). Descriptive analyzes indicated that the majority of participants had already been victims of prejudice based on sexual orientation. Through correlation analyses, it was identified that the responsiveness of parents or caregivers was associated with lower incidence of child abuse, experiences of enacted stigma and depression in adulthood. Although the averages pointed to low indicators of mental health problems, concealment of sexual identity was a predictor of depression, anxiety and stress. It was also verified that mistreatment perpetrated by pairs contributed to explain stress. Study 2, entitled “Disclosure of Sexual Orientation, Prejudice and Violence: What is the Role of Parents?” aimed to understand the process of disclosure of sexual orientation, experiences of prejudice and violence motivated by sexual orientation and perceptions about parent’s role in relation to these situations. The study was qualitative and exploratory. Seven men self-identified as homosexual with ages between 19 and 33 were participants. Participants answered a semi-structural interview that occurred individually. The analyses were performed through Thematic Analysis. It was identified that the disclosure of sexual orientation to parents was conducted voluntarily and involved the need to share a central aspect of personal identity. Initial reactions of parents were negative, with the majority failing to provide emotional support to their children. Prejudice and violence began in childhood and were part of the daily life of participants in the form of tricks, humiliations and physical abuse. Although they generated feelings of anger and sadness, issues related to prejudice and violence were not treated with parents.